Gently does it!: in situ preparation of alkali metal–solid electrolyte interfaces for photoelectron spectroscopy - Gibson, JS; Narayanan, S; Swallow, JEN; Kumar-Thakur, P; Pasta, M; Lee, T-L; Weatherup, RS (Royal Society of Chemistry, 2022)
The key charge transfer processes in electrochemical energy storage devices occur at electrode–electrolyte interfaces, which are typically buried, making it challenging to access their interfacial chemistry. In the case of Li-ion batteries, metallic Li electrodes hold promise for increasing energy and power densities and, when used in conjunction with solid electrolytes, the adverse safety implications associated with dendrite formation in organic liquid electrolytes can potentially be overcome. To better understand the stability of solid electrolytes when in contact with alkali metals and the reactions that occur, here we consider the deposition of thin (∼10 nm) alkali metal films onto solid electrolyte surfaces, where the metal is thin enough that X-ray photoelectron spectroscopy can probe the buried electrode–electrolyte interface. We highlight the importance of in situ alkali metal deposition by assessing the contaminant species that are present after glovebox handling and the use of ‘inert’ transfer devices. Consequently, we compare and contrast three available methods for in situ alkali-metal deposition; Li sputter deposition, Li evaporation, and Li plating induced by e− flood-gun irradiation. Studies on both a sulphide solid electrolyte (Li6PS5Cl), and a single-layer graphene probe surface reveal that the more energetic Li deposition methods, such as sputtering, can induce surface damage and interfacial mixing that are not seen with thermal evaporation. This indicates that the appropriate selection of the Li deposition method for in situ studies is required to observe representative behaviour, and the results of previous studies involving energetic deposition may warrant further evaluation.